Understanding Trust in Organizations A Multilevel Perspective - Gillespie, Nicole; Fulmer, Ashley; Lewicki, Roy (Taylor & Francis, 2021)
network trust, trust, second-hand trust, prototrust, relational trust, network theory, mechanism, indicators, contingencies, tie strength, social distance, network closure, vertical network differentiation, governance veracity, identity authenticity, swift trust